Retificando uma interpretação: o uso de um artigo de Gaston Bachelard como pretexto para a crítica a interpretação de um experimento crucial - Melo, Jairo de Sousa (2009)
Basically, this work is about the origins of the Theory of Relativity. However, most importantly, it intends to interpret how and in which ways the Michelson´s experiment may have contributed or not to ideas that led Einstein in developing his seminal theory. Most specifically, this work leans over a text of 1949, by philosopher Gaston Bachelard in which he, in according with common sense of his age, declare that the experiment made by Michelson in 1881 is the starting point of the development of Theory of Relativity. At last, this paper made a comparative analysis of Einstein s own statements and a demonstration that, although the experiment had been crucial to resolve the ether problem, it, that is, its result, doesn t bear any significant value in the theories developed by the physicist, and, beyond that, contrary to what was postulated, the theory explains the failure of the experiment, its null result; and this result didn t lead, in its age, to any postulation about the subjacent principle to Theory of Relativity